Hubungan Kekerabatan Ikan Kerapu Sunu (Plectropomus spp.) di Desa Liang Kabupaten Banggai Kepulauan Berdasarkan Karakter Morfologi - Mustikawati, Ni Luh Ayu; Budiarsa, I Made; Kundera, I Nengah; Ramadhan, Achmad; Jayanti, Zulaikhah Dwi; Ashari, Abdul (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to determine the phylogenetic relationship of coral trout groupers (Plectropomus spp.) in the waters of Liang Village, Banggai Kepulauan Regency, based on morphological characters. The research employed a descriptive exploratory method with quantitative and qualitative approaches. Samples were collected using purposive sampling, obtaining 15 individuals representing five species: Plectropomus leopardus, Plectropomus oligacanthus, Plectropomus maculatus, Plectropomus areolatus, and Plectropomus leavis. Morphological observations included 25 morphometric characters, 11 meristic characters, and 4 qualitative characters. Data were analyzed using Principal Component Analysis (PCA) to identify the main morphological characters contributing to variation among species, followed by cluster analysis using the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) to assess phylogenetic relationships. The results indicated that the physicochemical conditions of the waters in Liang Village were suitable to support coral trout grouper populations. PCA results showed that the first two principal components (PC1 and PC2) explained 73.31% of the total morphological variation, with interorbital length, dorsal fin base length, and body depth contributing most significantly to species differentiation. The UPGMA dendrogram revealed that Plectropomus leopardus exhibited the closest phylogenetic relationship with Plectropomus areolatus and Plectropomus oligacanthus, while Plectropomus maculatus showed the greatest morphological divergence and formed a separate cluster. These findings demonstrate that morphological characters are effective in revealing phylogenetic relationships among Plectropomus species in the studied waters.